2020
DOI: 10.1002/hep.31112
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Particles Activate Toll‐Like Receptor 2 Signaling Initially Upon Infection of Primary Human Hepatocytes

Abstract: BaCKgRoUND aND aIMS: To date, conflicting data exist as to whether hepatitis B virus (HBV) has the ability to induce innate immune responses. Here, we investigated cellular changes after the first contact between HBV and primary human hepatocytes (PHH) in vitro and in vivo. appRoaCH aND ReSUltS: The exposure of PHH to HBV particles resulted in nuclear translocation of NFκB, followed by the expression and secretion of inflammatory cytokines (IL [interleukin] 1B, IL6, and TNF [tumor necrosis factor]). Ultraviole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 45 publications
2
50
1
1
Order By: Relevance
“…The HBVinduced gene expression profile was comparable to that of a TLR2 ligand (Pam3Cys) but distinct from those known as viral sensors, TLR3 or TLR7/9. These findings contrast with the abovementioned stealth properties of HBV (Zhang et al 2020). On the other hand, Guo et al (2009) studied the effect of the PRRs adaptors (TRIF, RIG-1/MDA5, IPS-1) on HBV + co-transfected cells (HepG2 and Huh7).…”
Section: Hepatitis Bcontrasting
confidence: 57%
“…The HBVinduced gene expression profile was comparable to that of a TLR2 ligand (Pam3Cys) but distinct from those known as viral sensors, TLR3 or TLR7/9. These findings contrast with the abovementioned stealth properties of HBV (Zhang et al 2020). On the other hand, Guo et al (2009) studied the effect of the PRRs adaptors (TRIF, RIG-1/MDA5, IPS-1) on HBV + co-transfected cells (HepG2 and Huh7).…”
Section: Hepatitis Bcontrasting
confidence: 57%
“…Its interplay with the signaling pathways leading to IFN production is still a matter of debate. Some publications have described a type I and III IFN or pro-inflammatory response to HBV infection in cultured hepatocytes [3][4][5][6][7]. HBV may also induce pro-inflammatory cytokines in immune cells such as Kupffer cells, the liver macrophages, even if they are not productively infected [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, a report was published suggesting that HBV stimulates the TLR-2 pathway leading to NF-κB activation and production of pro-inflammatory cytokines [7]. The authors suggested that a receptor-binding mechanism might be involved in this response.…”
mentioning
confidence: 99%
“…However, lipoprotein contamination of the TLR2/4 pathway originating from the bacterial purification system could not be excluded 4,5 . Our recent studies indicated TLR2 as a contributor to T cell-dependent hydrodynamic HBV infection clearance in mice and primary human hepatocyte recognition of nascent HBV particles by TLR2 towards the activation of anti-HBV immune responses in vitro which challenges the former classification of HBV as "stealth" virus 6,7 . Moreover, impacting of TLR activation on the glycolytic metabolism drives macrophage and T-cell activation, suggesting TLR regulation of mTOR-integrated immune and metabolic processes [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 93%
“…Our previous studies showed that exposure of hepatic cells including hepatocytes, liver sinusoidal cells, and Kupffer cells to HBVs or the canonical TLR2 ligand P3C resulted in diverse cellular responses 6,[23][24][25][26] . Thus, now we asked whether and how exposure of B cells to HBVs changes their activation status.…”
Section: Activation Of B Cells Tlr2 Impacts the Akt-mtor Pathway And mentioning
confidence: 99%